WEB-BASED SCHOOL INFORMATION SYSTEM AT SMA PGRI 2 KAYEN PATI - Listiyani, Nindy Aprilia; Meimaharani, Rizkysari; Nurkamid, Mukhamad (Jurnal Dialektika Informatika (Detika), 2024)
The PGRI 2 Kayen Pati High School Academic Information System was created to make it easier for schools to process academic data, including information about students, teachers, classes, subjects, non-academic assessments, life skills, extracurricular activities, academic assessments, skills assessments, and report card information (academic, non-academic, extracurricular, lifeskill, and skills data). In light of this, the goal of this project is to develop an information system that will make grading easier and provide online grade information. Because of its flexibility, the waterfall model was adopted in the system's design process. The MySQL database and PHP programming language are used in this information system. An academic information system that can assist teachers in managing grades and show the ranking of students in each class is the outcome of this project.